Integrative culture traditional and participatory sustainable development dynamics: between optional and compulsory solidarity tradition. -Almizabi Community model - HAMADI, Mohamed Cherif; DJERIOU, Slimane (Social Sciences Journal, 2021)
One of the objectives of sustainable development drives in pursuit of rational and rationalize the available capacities, striving to maintain the greatest possible beneficial achievements either natural or manufactured as a haunting future generations, and so are its integrity from the central to addressing the determinants Available dimensions and thus contribute more in Bougainville to achieve the desired lasting element, but realized that organic Association newly arising between them and the cultural factor to be participatory traditional practices emerging field, numerous research jurisdictions Her studies, so the motivation to higher social solidarity tendency of coordinating indicators for sustainable development programmes and plans raised locally, So the motivation to higher social solidarity tendency of indicators sustainability of programmes and coordinating development plans raised locally, and analytical study of effects and attended pros, mechanisms for promoting a culture of participatory tendency within traditional society in our country, has a responsibility to maintain Active diversification and sense embodied in many physical and cultural evidence dematerialization, it found these participatory culture Espace vital mandatory civil society’s collective imagination "big almizabi" then through continuity in the optimization and balanced resources And the available capabilities.